2011
DOI: 10.1105/tpc.111.088377
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-Dependent Cell Cycle Reactivation through Transcriptional Regulation ofArabidopsis E2Faby Lateral Organ Boundary Proteins

Abstract: Multicellular organisms depend on cell production, cell fate specification, and correct patterning to shape their adult body. In plants, auxin plays a prominent role in the timely coordination of these different cellular processes. A well-studied example is lateral root initiation, in which auxin triggers founder cell specification and cell cycle activation of xylem polepositioned pericycle cells. Here, we report that the E2Fa transcription factor of Arabidopsis thaliana is an essential component that regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(176 citation statements)
references
References 72 publications
1
173
0
2
Order By: Relevance
“…In Arabidopsis, AtE2FA is required for lateral root initiation and vascular patterning (Berckmans et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, AtE2FA is required for lateral root initiation and vascular patterning (Berckmans et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…During LR initiation, LBD16 has been shown to play an important role promoting asymmetric cell division of LR founder cells, controlling polarized nuclear migration to the common cell pole between pairs of founder cells (Goh et al, 2012). LBD18 and LBD33 positively regulate the cell cycle via the transcriptional regulation of E2Fa (Berckmans et al, 2011). LBD29 has also been reported to be involved in the regulation of the cell cycle progression during LR formation (Feng et al, 2012).…”
Section: Lbd29 Is Expressed In the Lrp And Cells Directly Overlying Tmentioning
confidence: 99%
“…Several LBD proteins have been reported to interact with other family members or distinct classes of transcription factors that may help confer target specificity. For example, LBD18 and LBD33 dimerize to regulate cell cycle by activating E2FA transcription during LR initiation (Berckmans et al, 2011) and LBD6 (AtAS2) interacts with a MYB transcription factor AtAS1 during leaf development (Xu et al, 2003). In summary, LBD family members play key regulatory roles throughout plant development, including LBD16, LBD18 and LBD29, which are critical for LR development.…”
Section: Lbd29 Is Expressed In the Lrp And Cells Directly Overlying Tmentioning
confidence: 99%
“…Among the LBDs-SRDX that we tested, LBD16-SRDX inhibits LR initiation most efficiently, strongly suggesting that LBD16/ASL18 is one of the key regulators for ACDs of the LR founder cells ( Recently, Berckmans et al (Berckmans et al, 2011) reported that LBD18/ASL20 and LBD33/ASL24 function as a heterodimer and regulate the cell cycle reactivation on LR initiation through transcriptional activation of cell cycle controller, E2Fa (Berckmans et al, 2011). LBD18/ASL20 is also involved in the LR primordium development and emergence (Lee et al, 2009), as well as in the xylem tissue differentiation (Soyano et al, 2008).…”
Section: Research Articlementioning
confidence: 99%